Physics of Entropy Growth and Thermal Radiations - Ivanov, M. Ja. (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
An in-depth analysis of the entropy growth nature and thermal radiation is performed. The consideration in theoretical terms is entirely based on the complete system of the initial conservation laws of gas dynamics and thermodynamics. The properties of generalized solutions for conservation equations of mass, momentum and energy are studied. We demonstrate the luminescence of shock waves and radiation equilibrium of high temperature jets, expiring from the aviation and rocket engine nozzles. We show the relationship of the entropy growth with total pressure losses in the tasks of aero physics.